NEW PTEROSAUR SPECIMENS FROM THE KEM KEM BEDS (UPPER CRETACEOUS, CENOMANIAN) OF MOROCCO (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
Although pterosaurs from Africa are still rare, in recent years several specimens have been described from the Kem Kem beds (Upper Cretaceous, Cenomanian) of Morocco. Here we describe four additional specimens from this informal lithostratigraphic unit: a jaw fragment, two mid-cervical vertebrae, and a humerus. All these specimens show three-dimensional preservation, differing much from the flat condition found in most pterosaur material. The vertebrae are particularly well preserved, and allow accurate observations on the pneumatization of the neural arch. Based on comparable material, we show that at least two edentulous pterosaur species were present in this informal lithostratigraphic unit, thus adding to the growing evidence of considerable pterosaur diversity in northwestern Africa during the "middle" Cretaceous. So far, the Kem Kem beds have the most diverse pterosaur fauna in this continent, with the presence of anhanguerids, azhdarchids, pteranodontids, and tapejarids.
Keywords: Pterosauria; Azhdarchidae; Morocco; Cretaceous; Cenomanian; Kem Kem beds